2022
DOI: 10.1101/2022.02.03.478939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

2’-O-methylation of the second transcribed nucleotide within mRNA 5’ cap impacts protein production level in a cell specific manner and contributes to RNA immune evasion

Abstract: In higher eukaryotes, m7G-adjacent nucleotides undergo extensive modifications. Ribose of the first or first and second transcribed nucleotides can be subjected to 2'-O-methylation to form cap1 or cap2, respectively. Additionally, when the first transcribed nucleotide is adenosine, it can not only undergo 2'-O-methylation but can also be methylated at position N6 forming N6,2'-O-dimethyladenosine (m6Am). Recent studies have shed some light on the functions of cap1, showing that cap1 in mammalian cells plays a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Furthermore, these pathways could also influence the regulation of immune cells. Recently, a study reported that the cap structure of m7G can induce immune evasion by enhancing the identity of RNA as a ‘self-molecule’ for cellular recognition factors [ 32 ]. This finding might explain why the cluster was mainly involved in immune-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these pathways could also influence the regulation of immune cells. Recently, a study reported that the cap structure of m7G can induce immune evasion by enhancing the identity of RNA as a ‘self-molecule’ for cellular recognition factors [ 32 ]. This finding might explain why the cluster was mainly involved in immune-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro transcribed mRNAs transfected into cells were differentially processed and translated in two different cell types depending on sequence and methylation status. [ 61 ] Hence, 5′UTR heterogeneity resulting from RNA Pol II promoters with multiple initiation sites can impact on translation efficiency (Figure 2) for differential regulation during development or in response to changing conditions. Here, addition of cOMe to some transcripts but not others could further increase the potential for differentially regulating gene expression, particularly in the context of local translation in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ] Although this analysis has some bias from interference with transcription for some sequences, in vitro transcribed mRNAs transfected into cells were differentially processed and translated in two different cell types depending on sequence and methylation status. [ 61 ]…”
Section: Heterogeneous Transcription Start Sites: a Novel Layer Of Ge...mentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted February 2, 2023. ; https://doi.org/10.1101/2023.01.30.526332 doi: bioRxiv preprint Page11 methylation, which commonly locates at the 2'-OH position of ribose (Ayadi et al, 2019;Drazkowska et al, 2022).…”
Section: Prediction Of Methylinosine and Formyluridine Analogs Enrich...mentioning
confidence: 99%